SEJARAH TAFSIR AL-QURAN PADA ERA TABI’IN DAN KODIFIKASI AWAL DALAM KAZANAH KEILMUAN ISLAM - Mohammad Nurul Burhan; Ahmad Manshur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Qur’anic exegesis (tafsir) constitutes a significant component of the Islamic intellectual tradition and has continuously developed in response to the social, intellectual, and historical dynamics of the Muslim community. This article aims to examine the historical development of Qur’anic exegesis during the era of the tābi‘īn and the early period of codification, as well as its contribution to the growth of Islamic scholarship. This study employs a qualitative method with a library research approach, emphasizing historical and descriptive-analytical analysis of classical and contemporary tafsir literature. The findings indicate that during the era of the tābi‘īn, Qur’anic interpretation was predominantly characterized by tafsir bi al- ma’thūr, which relied on the Qur’an itself, the Prophetic traditions (hadith), and the reports of the Companions, although limited forms of ijtihād began to emerge in response to the increasingly complex needs of the Muslim community. The development of tafsir during this period was also marked by the emergence of tafsir schools in various Islamic regions, such as Mecca, Medina, and Iraq, each exhibiting distinctive interpretative tendencies. Furthermore, the early codification of Qur’anic exegesis represents a crucial milestone in the history of tafsir, as it played a vital role in preserving the authenticity of interpretation, expanding the transmission of knowledge, and laying the foundation for tafsir as an independent and systematic scholarly discipline. Thus, the era of the tābi‘īn and the early codification period constitute fundamental phases that shaped the direction, methodology, and scholarly tradition of Qur’anic exegesis within the Islamic intellectual heritage.